Katalin Varga - Strickland, Peter; Györi, Márk; Péter, Hilda; Gavriliu, Andrea; Giacomello, Roberto
Not the least surprising aspect of this sombre Romania-set revenge drama is that it's written and directed by a man born in Reading, England. But Peter Strickland, foreigner though he is, seems to know exactly how the land lies. It tells of a woman (Hilda Peter) who's driven from her home by her husband and, young son in tow, begins a search for the men who raped her ten years before. But this is to say nothing of the odd and unsettling atmosphere the film generates, largely due to the haunting photography of the landscape – the repeated shot of a forest is deeply spooky – and the incidental music by Steven Stapleton and Geoff Cox. At times we seem to be watching the reconstruction of an ancient folk tale, and Strickland, as if entrusted with its telling, hardly puts a foot wrong. [www.independent.co.uk]